PENGARUH BAURAN PROMOSI, ATRIBUT PRODUK, DAN KUALITAS LAYANAN TERHADAP TINGKAT PENGETAHUAN MAHASISWA DAN BERIMPLIKASI PADA KEPUTUSAN MEMILIH PERGURUAN TINGGI (Studi pada Sekolah Tinggi Ilmu Farmasi âYayasan Pharmasiâ Semarang) - Daniel Yeri Kristiyanto, 12.5202.0161; Yulianto, Heru (Jurnal Mahasiswa Pasca Sarjana, 2014)
Decision of choosing a college is influenced by several things. This research analyzes the influences of promotional mix, product attribut, and servqual to the level of knowledge and consumer decision to choose implications for higher education. The proposed research problem fully research gaps from previous reseaches, that shows positive and negatif influence. The variables and indicators of researh based on the previous research. There is a model that have been developed and seven hypotheses to answer these research problems. Respondents of this study is a new student of Sekolah Tinggi Ilmu Pharmasi âYayasan Pharmasiâ Semarang. Responden from this research are 100 people. Data analyze tools which used in this reseach is Structural Equation Modeling (SEM) under IBM SPSS AMOS Version 20 program. Result from data analyzes shows that the model and the result from research can be accepted. And that result proves that all eksogenous variables influences positive and significant to the endogenous. Managerial implication in this research gives suggestion for company to pay more attention in promotion, services quality, and quality of product education. Keywords : Promotional mix, Product Attribute, Service Quality, Consumer Knowledge, Decision to choose.